PEMBEKALAN PEGAWAI NEGERI SIPIL YANG AKAN PURNA TUGAS DI LINGKUNGAN PEMERINTAH KOTA MAGELANG - Astuti, Sukoariyah Sri Puji (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2019)
Towards retirement, civil servants should have prepared themselves to be able to live theirretirement later well. But in reality not all retired civil servants can live it well. Seeing the phenomena that occur in the field requires preparation for prospective pensioners. The Magelang City Education and Training Personnel Agency has prepared debriefing for Magelang City Civil Servants who will be on duty. This paper aims to provide information about